Ressignificar para manter-se fiel: Dom Helder Câmara e o exercício do seu ministério sacerdotal (1955-1965). - Pina Neta, Lucy da Silva (2019)
This thesis aimed to analyze, through the theoretical-methodological mechanisms of the indiciary paradigm proposed by Carlo Ginzburg, how did Helder Pessoa Camara, the late Archbishop of Olinda and Recife, exercise and re-signify his priestly ministry between 1955 and 1965. The main assumption of the research was that during this period there was a deep inner transformation of Dom Helder, which was translated into what later became known as the "social turn" of his priestly practice, and that such a spiritual movement - that lead to increasingly advanced practices in the social field - can be followed by his writings, both public and private. We used as an initial analytical framework the year of realization of the XXXVI International Eucharistic Congress, held in Rio de Janeiro in 1955, organized by him on behalf of Cardinal Jaime de Barros Camara, of whom he was Auxiliary Archbishop. As a final mark, the year of his return to Recife, after the closing of the Second Vatican Council, in December 1965. For the development of this thesis we considered the documents retrieved and deposited in the Archives of the Dom Helder Camara Institute in Recife, especially collections of active correspondence, notebooks, and spiritual retreat schemes. They were analyzed in this thesis, above all, as the most common instrument through which Dom Helder wrote about himself and his role as social operator of the sacred. We analyzed the continuities, discontinuities and resignifications of the contents in which he attributes to the diurnal exercise, taken very seriously, the social role of a priest, also through a critical historicization and a chronology that not only took into account biographical facts about Dom Helder, but all the juncture in which he was involved.